GAMBARAN KECERDASAN EMOSIONAL SISWA KELAS VII SMP NEGERI 9 CIMAHI SELAMA PEMBELAJARAN DARING - Anisa Dwi Lestari; Euis Eti Rohaeti; Riesa Rismawati Siddik (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2022)
The current situation in Indonesia is the covid 19 pandemic makes the government (ministry of education) apply online learning or distance learning (PJJ) regulations. Which we don't realize this affects the emotional intelligence of students. The purpose of this study is to find out the picture of emotional intelligence of students of class VII SMPN 9 Cimahi during online learning. This research uses qualitative descriptive methods. Data collection techniques use interviews, interviews and documentation. Based on the results of research in SMPN 9 Cimahi there are two categories of emotional intelligence students, measurements of low emotional intelligence category and high emotional intelligence are measured by the results of emotional intelligence questionnaire scores that have previously been given by BK teachers, students with high emotional intelligence students are able to learn emotions and express in positive things and students with low emotional intelligence focused on two indicators that have not been able to facilitate attention to the task being done and do not have the ability to communicate with others.Keywords: Emotional Intelligence, Class VII Students, Online Learning.